JSE 31:3 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2017)
I’ve often noticed how debates within the SSE community sometimes parallel debates in the political arena, perhaps especially with respect to the passion they elicit and the intolerance and condescension sometimes lavished on members of the “opposition.” Occasionally, of course, the debates in the SSE are nearly indistinguishable from those in the political arena—say, over the evidence for human-caused climate change. But what I find most striking is how the passion, intolerance, etc.—perhaps most often displayed by those defending whatever the “received” view happens to be—betrays either a surprising ignorance or else a seemingly convenient lapse of memory, one that probably wouldn’t appear in less emotionally charged contexts. What impassioned partisans tend to ignore or forget concerns (a) the tentative nature of both scientific pronouncements and knowledge claims generally (including matters ostensibly much more secure than those under debate), as well as (b) the extensive network of assumptions on which every knowledge claim rests. So I’d like to offer what I hope will be a perspective-enhancer, concerning how even our allegedly most secure and fundamental pieces of a priori knowledge are themselves open to reasonable debate. A widespread, but naïve, view of logic is that no rational person could doubt its elementary laws. But that bit of popular “wisdom” is demonstrably false. And if that’s the case, then so much the worse for the degree of certitude we can expect in more controversial arenas. Let me illustrate with a few examples.1